The Impact of a Collaborative IoT Framework for Smart Cities and Environmental Monitoring - Husein, Suzan; Mudhafar, Darun; B, Saravana Balaji (International Journal of Interactive Mobile Technologies (iJIM), 2023)
this paper proposed an architecture that is SenSquare, it is capable to carry various data sources which is coming through an open IOT program and throng sensor campaign, as well as displaying an integrated access for the utilizers. The goals of smart cities are to progress the quality of citizen in life through leveraging details on process of the urban scales that removed by diverse data source gathered at city broad deployment. In this paper checking the whole surfaces of a compound system, traversing through problems of various quality, this paper contract with the diverse data ranking, the Mobile Crowd sensing (MCS) administration to data ecological, acting information and integration, the services of IOT installation and redeployments. This study explained the suggested resolutions in cooperation with a functions and current ways to sitting unlock defies. Eventually, it pretends the ability of the SenSquare by jointly the desktop client and mobile.